Synthesis and Antimicrobial Activity of Some Mannich Bases of Benzimidazolyl Substituted 1H-Isoindole-1,3(2H) Diones - Rajpurohit, Sangeeta; Sah, Pramilla (Asian Journal of Chemistry, 2016)
The synthesis of some Mannich bases from benzimidazole substituted 1H-isoindole-1,3(2H) diones have been reported. The compounds were evaluated for their antibacterial and antifungal activity. The screening results have shown greater inhibition against fungi than against bacterial strains.